Soloalbum - Stuckrad-Barre, Benjamin von 1975- (Concorde Home Entertainment, 2003)
Ben, a music journalist, deals with the breakup with his girlfriend, Katharina, by trying everything possible, including trying to win Katharina back.
Bildformat: 2.35:1 (16:9 anamorph)
Orig.: Deutschland 2003
Enth. Hinter den Kulissen ; Cast und Crew Infos ; Castingszenen ; Outtakes ; Produktionsnotizen ; Musikvideo von "Sportfreunde Stiller" ; Solo-Jingles von Autor Stuckrad-Barre und friends ; Audiokommentar von Matthias Schweighöfer und Nora Tschirner ; Audiokommentar von Gregor Schnitzler und Christoph Müller
Keywords: Feature films; Man-woman relationships -- Drama; Foreign films; Romantic comedy films